Algorithm for choosing the best available technology - V. I. Bondarenko; O. V. Eremenko; Yu. V. Tretyakova (Тонкие химические технологии, 2011)
The article describes the main principles and a model of ecological-economic analysis of the best available technology. It is shown that when choosing a technology, one must take into account the influence exerted on the environment by the processes associated with the production of the materials used, raw materials and energy, as well as the aftereffects caused by waste products.